(untitled) (Journal of the College of Education for Women, 2019)
Aspect-Oriented Software Development (AOSD) is a technology that helps achievingbetter Separation of Concern (SOC) by providing mechanisms to identify all relevant pointsin a program at which aspectual adaptations need to take place. This paper introduces abanking application using of AOSD with security concern in information hiding.